DESKRIPSI PENGETAHUAN IBU TENTANG TUMBUH KEMBANG BALITA DI TK PESISIR ELA-ELA KECAMATAN UJUNG BULU KABUPATEN BULUKUMBA - Jusni; Sulastri; Sumarni; Serly (JMNS, 2020)
Good quality children can be achieved by ensuring that the child's development process is also good. Such as height, weight, and head circumference. While develospment is a gradual change and increase in abilities, such as motor skills, sensory, language and social goals, to determine the description of mother's knowledge about toddler growth and development methods, this type of research uses descriptive quantitative methods. The number of samples is 35 respondents. The results of the description of the knowledge of mothers about the growth and development of children under five are mostly sufficiently knowledgeable, 23 respondents (45.7%) were in the poor category as many as 19 respondents (54.3%). Conclusion: The description of the mother's knowledge about the growth and development of children under five is mostly sufficiently knowledgeable, 23 respondents (65.7%), 16 respondents (54.3%) in the gross motoric category were sufficient.